PELATIHAN & PENDAMPINGAN PEMBUATAN PRODUK PUPU’ KHAS MANDAR DARI IKAN TERBANG PADA KELOMPOK MOSSO INDAH & SEAMASEI DI KELURAHAN MOSSO, SULAWESI BARAT - Nur, Muhammad; Tenriware, Tenriware; Tikawati, Tikawati; Nasyrah, Adiara Firdhita Alam; Ihsan, Muhammad Nur; Ayuandiani, Wulan; Sapri, Rasti; Said, Muhammad (Universitas Mataram, 2025)
Mosso Village, located on the coast of West Sulawesi, has abundant fishery resources, especially flying fish. However, its utilization is still limited to consumption in the form of fresh, smoked, and dried fish, so it has not provided optimal economic value. This condition encourages the need for innovation in fishery product processing to add value and sustainability. One of the efforts made is through training and assistance activities based on coastal community empowerment. The purpose of the activity is to increase the knowledge and skills of the community in processing flying fish into high economic value pupu' products, while strengthening the capacity of the Mosso Indah and Seamasei groups as local business actors. The activity methods include material delivery, demonstrations, and direct practice of making flying fish pupu'. The activity was held on August 31, 2025, at Café Inna, Labuang Neighborhood, Mosso Village, and was attended by 40 participants from the two groups. Knowledge measurement was conducted using pre-tests and post-tests on a scale of 0–100, while skills were assessed on a scale of 1–4. (40 words) The results showed an increase in participants' average knowledge score from 56.2 to 88.5 after the training. A total of 87.5% of participants achieved a skill level of ≥3, indicating good ability in the production and packaging of pupu'. During the activity, one flying fish pupu' product was produced according to standards. Participants showed high enthusiasm to continue production independently and began to form local group-based marketing networks. In conclusion, the training and mentoring activities for making flying fish pupu' succeeded in increasing the knowledge and skills of coastal communities and have the potential to strengthen sustainable local economic independence.